2013
DOI: 10.1519/jsc.0b013e3182736e31
|View full text |Cite
|
Sign up to set email alerts
|

Do the Noncaffeine Ingredients of Energy Drinks Affect Metabolic Responses to Heavy Exercise?

Abstract: Energy drinks (EDs) such as Red Bull (RB) are marketed to enhance metabolism. Secondary ingredients of EDs (e.g., taurine) have been purported to improve time trial performance; however, little research exists on how such secondary ingredients affect aerobic metabolism during heavy exercise. The purpose of this study was to investigate the effect of the secondary ingredients of RB on aerobic metabolism during and subsequent to heavy exercise. In double-blind, counterbalanced, and crossover fashion, 8 recreatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In line with this study, other recent studies did not show any ergogenic effects of taurine supplementation in different forms of exercise (Pettitt et al 2013). Pettitt et al (2013) did not show improvements in the aerobic metabolism (accumulated oxygen consumed and EPOC) after acute ingestion of an energy drink (caffeine + taurine) or control drink (equivalent caffeine content alone).…”
Section: Discussionsupporting
confidence: 89%
“…In line with this study, other recent studies did not show any ergogenic effects of taurine supplementation in different forms of exercise (Pettitt et al 2013). Pettitt et al (2013) did not show improvements in the aerobic metabolism (accumulated oxygen consumed and EPOC) after acute ingestion of an energy drink (caffeine + taurine) or control drink (equivalent caffeine content alone).…”
Section: Discussionsupporting
confidence: 89%
“…However, caffeine and carbohydrate may act in a synergistic manner [182]. To support this view, a recent paper by Pettitt et al [186] reported that while ingestion of an ED prior to exercise affected aerobic metabolism during and following cycling exercise, the secondary ingredients found in the ED had no additive effects.…”
Section: Exercise Performancementioning
confidence: 99%
“…The ergogenic impact of caffeine is supported by a plethora of studies [8,26,30,34,35]. However, caffeine intake can provoke side effects such as headache, hypertension, tachycardia and gastrointestinal upset [11,51] and acts differently in every athlete [70].…”
Section: Discussionmentioning
confidence: 99%